2001
DOI: 10.1097/00005768-200102000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptoms and exercise-induced asthma in the elite athlete

Abstract: Although questionnaires provide reasonable estimates of EIA prevalence among elite cold-weather athletes, the use of self-reported symptoms for EIA diagnosis in this population will likely yield high frequencies of both false positive and false negative results. Diagnosis should include spirometry using an exercise/environment specific challenge in combination with the athlete's history of asthma symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
218
2
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(242 citation statements)
references
References 0 publications
14
218
2
8
Order By: Relevance
“…Recently, Anderson et al (7,16) as well as Fitch (17) (2) showed in a questionnaire-based report a prevalence of doctor-diagnosed asthma of 14% in 155 actively competing skiers compared with 5% in twice-matched controls; moreover, the prevalence of asthma diagnosis increased with increasing age in the actively competing skiers. This was followed by reports of high prevalence in Norwegian and Swedish skiers (18), in competitive figure skaters (19,20), in elite cold-weather athletes (21) and among participants in the 1998 American Olympic National team for winter sports including gold medallists (22).…”
Section: Asthma and Bhr Among Athletesmentioning
confidence: 97%
“…Recently, Anderson et al (7,16) as well as Fitch (17) (2) showed in a questionnaire-based report a prevalence of doctor-diagnosed asthma of 14% in 155 actively competing skiers compared with 5% in twice-matched controls; moreover, the prevalence of asthma diagnosis increased with increasing age in the actively competing skiers. This was followed by reports of high prevalence in Norwegian and Swedish skiers (18), in competitive figure skaters (19,20), in elite cold-weather athletes (21) and among participants in the 1998 American Olympic National team for winter sports including gold medallists (22).…”
Section: Asthma and Bhr Among Athletesmentioning
confidence: 97%
“…Our results are similar to those of previous studies suggesting that self-reported symptoms are not associated with testing positive when performing a standardized EIB test. 5,[15][16][17] This is clinically relevant from both an overdiagnosis and underdiagnosis perspective. A previous report indicated that the majority of physicians may overdiagnose and treat EIB with short-acting ␤ agonists based on symptoms alone, without assessing the athlete during an exercise challenge.…”
Section: Prevalence and Symptomsmentioning
confidence: 99%
“…The diagnosis of EIB in athletes, is often suspected by clinicians following an assessment of symptoms alone; with treatment frequently commenced without objective confirmation (4). This is despite evidence from several studies indicating that there is a poor relationship between the presence of respiratory symptoms and objective evidence of EIB (5)(6)(7)(8). It is thus recommended that respiratory symptoms should not be relied upon and that objective testing (e.g.…”
Section: Introductionmentioning
confidence: 99%